Designing an Automatic Room Temperature Control System for Smart Homes for the Elderly Using IoT - Rihhadatulaisy, Zakiyatunnisrina H.; Irianto, Kurniawan D. (International Journal Software Engineering and Computer Science (IJSECS), 2024)
The elderly population in Southeast Asia currently represents 8% or approximately 142 million people, according to the World Health Organization (WHO). As individuals age, various factors require greater attention, such as physical and mental health, a healthy and regular diet, as well as safety and comfort in their living environment. Extreme room temperatures often cause discomfort among the elderly, potentially worsening their health conditions. This study proposes the design of an automatic room temperature control system for smart homes, specifically for elderly care, utilizing Internet of Things (IoT) technology. The system employs a DHT22 sensor, alongside fans and heaters, to maintain stable room temperatures. The methodology includes problem identification, system overview, requirements identification, system and device design, system testing, and evaluation. The system measures room temperature using the DHT22 sensor and automatically regulates the fans and heaters to ensure a comfortable environment for the elderly. Test results indicate that the system effectively maintains room temperature stability. Furthermore, the system can be controlled remotely via the Blynk application, providing ease of use for the elderly in managing the system from a distance. This system thus aids the elderly in consistently maintaining a comfortable room temperature tailored to their specific needs.